Radon gas as a constructive element in the chilean pacific coast the case of a manor house in ViÃ±a del mar (valparaÃso). - Rizo Maestre, Carlos; A. SÃ¡ez, Claudio; B GonzÃ¡lez-AvilÃ©s, Ãngel; Galiano-GarrigÃ³s, Antonio; Echarri-Iribarren, VÃctor (International Journal of Engineering and Technology, 2018)
The presence of radon gas in buildings is an indicator of indoor air quality. The study presented analyses the amount of radon gas in the city of ViÃ±a del Mar in the Valparaiso region (Chile), in a manor house that currently serves as the Center of Advanced Studies at the Univer-sidad de Playa Ancha. Radon gas is an element considered highly harmful to people by various scientific agencies in the field of medicine and health, including the World Health Organization (WHO). The main effect of the presence of radon in the human environment is the risk of lung cancer. This radioactive gaseous element is present in almost all construction materials, and in the land where buildings are located. This article provides the measurements made by the Center of Advanced Studies of the Universidad de Playa Ancha and analyses the levels obtained according to their danger to humans. These values have been used as comparisons to analyse the differences in the presence of this gas between the Chilean Pacific coast and Europe. The values have been analysed with respect to the requirements that are currently being implemented.Â Â